The Quality and Acceptability of ‘Bakasi’ (Anguilla japonica) Cookies - Wilma C. Giango (European Scientific Journal, ESJ, 2016)
The study determined the quality and acceptability of ‘Bakasi’ (Anguilla japonica) Cookies. This sought to answer these objectives: find out bakasi powder formulation to enhance cookies and analyze the acceptability of bakasi cookies in terms of color, aroma, taste and texture. The study used the experimental research design in order to determine which of the three treatments representing different concentration levels of bakasi powder (120 grams, 90 grams, and 60 grams) produced better quality cookies. Sensory evaluation using 9 point Hedonic Rating Scale assessed the sensory qualities of the powder under study. Several trials were conducted using three treatments replicated thrice. The results of the study showed that the treatment 2 (Treatment 2) having a concentration mixture of 90 grams bakasi powder was considered to be the most acceptable compared with other treatments. The Quality and Acceptability of ‘Bakasi’ (Anguilla japonica) ingredients contributed to the cookie production business. Processing Bakasi cookies added to the realization of the new thrust in the country’s educational system to help the people in enhancing their knowledge and skills in the effective use of bakasi as one of the local raw materials and other resources in the community.